2015
DOI: 10.3109/13880209.2015.1079224
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids of Herba Epimedii stimulate osteogenic differentiation and suppress adipogenic differentiation of primary mesenchymal stem cells via estrogen receptor pathway

Abstract: Objective: The present study investigates the effect of total flavonoids of Herba Epimedii (HETF) on the osteogenesis and adipogenesis of primary MSCs. Materials and methods: HETF were prepared and identified by HPLC-fingerprinting, primary mouse MSCs in the presence of 0.006-6 mg/mL HETF for 2-10 d were subject to morphological, biochemical, and quantitative real-time PCR analysis. Results: Sixteen chemical components were identified in HETF by HPLC-fingerprinting and account for over 95% of the total area of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…A recent study revealed MIAT was an estrogen-inducible lncRNA and its expression was positively related to estrogen receptor (Li et al, 2018b). There was accumulating evidence to reveal that exposure of bone marrow stem cells to icariin or flavonoids of Herba Epimedii inhibited adipogenic differentiation, exhibiting decreased adipocyte numbers and downregulated mRNA expression of adipogenic differentiation markers, peroxisome proliferator‑activated receptor gamma (PPARγ) and CCAAT/enhancer‑binding protein α (C/EBPα) (Li et al, 2018c; Zhang et al, 2015); while treatment of bone marrow stem cells with estrogen receptor antagonist ICI182780 revered the effects of Herba Epimedii ingredient and promoted adipogenesis (Li et al, 2018c; Zhang et al, 2015). The study of Ihunnah et al (2014) also demonstrated activation of estrogen receptor in ASCs inhibited adipogenesis by decreasing the recruitment of the adipogenic PPARγ onto its target gene promoters, whereas the use of estrogen receptor antagonism ICI 182780 or knockdown of estrogen receptor-α via lentiviral shRNA enhanced adipogenesis by increasing the expression of PPARγ.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study revealed MIAT was an estrogen-inducible lncRNA and its expression was positively related to estrogen receptor (Li et al, 2018b). There was accumulating evidence to reveal that exposure of bone marrow stem cells to icariin or flavonoids of Herba Epimedii inhibited adipogenic differentiation, exhibiting decreased adipocyte numbers and downregulated mRNA expression of adipogenic differentiation markers, peroxisome proliferator‑activated receptor gamma (PPARγ) and CCAAT/enhancer‑binding protein α (C/EBPα) (Li et al, 2018c; Zhang et al, 2015); while treatment of bone marrow stem cells with estrogen receptor antagonist ICI182780 revered the effects of Herba Epimedii ingredient and promoted adipogenesis (Li et al, 2018c; Zhang et al, 2015). The study of Ihunnah et al (2014) also demonstrated activation of estrogen receptor in ASCs inhibited adipogenesis by decreasing the recruitment of the adipogenic PPARγ onto its target gene promoters, whereas the use of estrogen receptor antagonism ICI 182780 or knockdown of estrogen receptor-α via lentiviral shRNA enhanced adipogenesis by increasing the expression of PPARγ.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Herba epimedii flavonoids improve bone health by mediating the effects of RUNX2 on osteogenesis, strongly suggesting that it could be a novel agent for treating osteoporosis. 39 Similarly, Drynaria fortune can improve the proliferation and osteogenic differentiation of stem cells in the dental pulp in a dose-dependent manner. 40 At the same time, Icariin is a flavonoid with potent effects on bone marrow MSCs’ activity.…”
Section: Discussionmentioning
confidence: 99%
“…MSCs were identified by flow cytometry and differentiation capability and maintained in the culture medium at 37°C. Sodium fluoride (NaF) and 17 β -estradiol (ES) served as positive control for different experiments, and PBS was used as vehicle control [ 22 ].…”
Section: Methodsmentioning
confidence: 99%